Integrating environmental issues in the policy agenda by the ruling parties in East Java, Indonesia - Alim, Syahirul; Firmantoro, Verdy; Permadi, Angga Sukmara Christian (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This research explores how green ideologies are embedded in the policy agendas of ruling parties, including the three main political parties that won the 2020 local head elections in East Java Province, Indonesia. The research approach used is mixed methods, with quantitative and qualitative analysis to understand the awareness, discourse, and strategy of environmental issues in the policy agenda of the winning political parties. The results show that within political parties, sustainability considerations are largely reactive, oriented towards short-term goals, and mainly used for instrumental purposes. Despite the existing literature, parties that are more likely to survive electorally are in areas where voters are highly concerned about environmental issues and have different party strategies in terms of general policy. However, in East Java province, the increasing public concern for environmental issues has not been used as a strategic tool by political parties. These findings suggest that moving beyond superficial environmental initiatives towards strategic environmental integration can improve electoral competitiveness and promote sustainable development. The results suggest that by aligning their strategies with broader sustainability goals and adopting proactive measures for environmental management, regional political parties in East Java can not only respond to short-term electoral pressures; they can even begin to resolve some of the key sustainability challenges that underpin future electoral success and the quality of governance in their regions.